Study of Number, Shape, Size and Position of Mental Foramen in Bangladeshi Dry Adult Human Mandible - Hoque, Md Mesbahul; Ara, Shamim; Begum, Shahanaz; Kamal, AHM Mostafa; Momen, Md Abdul (Bangladesh Journal of Anatomy, 2014)
Context: Paralysis of the mental nerve is one of the principal complications of surgery of the mandibular canal and mental foramen region. Therefore, identification of mental foramen is important for dental surgeons in nerve block and surgical procedures like apico curettage of mandibular premolars, amalgam filling, peridental surgery etc. to avoid injury to neurovascular bundle. Verification of the existence of accessory mental foramina would prevent accessory mental nerve injury during periapical surgery. Therefore, prior knowledge of morphology and morphometry of mental and accessory mental foramen to particular block may cause effective mental block anaesthesia. Besides this, mental foramen and accessory mental foramen have been found to vary in position in different ethnic groups. So, it is important to study the morphology and morphometry of mental foramen. Materials and Methods: A cross-sectional, analytical type of study was conducted in the Department of Anatomy, Dhaka Medical College using dried adult human mandibles of unknown sexes. Number and shapes of mental foramen and accessory mental foramen were observed. Size and position were determined by using digital sliding calipers. Result: Mental foramen was present in all one hundred and eighty five (185) observed mandibles and it was bilateral. Accessory mental foramen was present in 1.62% on left side while on right side, it was 0.54%. None of the mandibles presented with bilateral accessory mental foramen. Shape was predominantly oval with 55.7% on right side and 53.5% on left side while it was round in 44.3% on right side and 46.5% on left side. Mental foramen was commonly located between 1st and 2nd premolar, below 2nd premolar and between 2nd premolar and 1st molar. Conclusion: Prior knowledge of mental foramen variations helps surgeon in planning surgery in that region to avoid nerve damage and also for effective mental nerve block anaesthesia. DOI: http://dx.doi.org/10.3329/bja.v11i1.20501 Bangladesh Journal of Anatomy, January 2013, Vol. 11 No. 1 pp 7-10